Time trends over five decades, and recent geographical variation, in rates of childhood squint surgery in England. Issue 6 (10th April 2013) - Chou, Munazzah R; Malik, Aeesha N J; Suleman, Mehrunisha; Gray, Muir; Yeates, David; Goldacre, Michael J
Abstract : Aims: To study trends in rates of childhood squint surgery in England over five decades, and to study recent geographical variation in England. Methods: Use of routine hospital statistics to analyse trends in squint surgery in the Oxford record linkage study area 1963–2010, and England 1968–2010; analysis of geographical variation in England 1999–2010. All rates, numerators and population denominators were restricted to people aged under 15 years. Results: The study included 519 089 admissions for operations on squint. Annual admission rates for squint surgery in England fell from 188.8 episodes per 100 000 population (95% CI 180.9 to 196.8) in 1968 to 64.1 (62.4 to 65.7) episodes per 100 000 population in 2010. A similar decline was seen in the Oxford region, from 213.2 (181.3 to 245.2) episodes per 100 000 population in 1963 to 61.3 (54.8 to 67.9) episodes in 2010. There was wide variation across local authorities in annual rates of squint surgery from 28.2 (95% CI 22.7 to 34.8) admissions per 100 000 population to 138.6 (123.0 to 155.7) admissions per 100 000, a 4.9-fold difference between areas with the highest and lowest rates. Conclusions: Squint surgery rates have decreased substantially over time. The current wide geographical variation in rates raises questions about whether this scale of variation is clinically warranted, whether it reflects variation in needs for surgery and patient/parental choice, whether it is a result of inequalities in the availability of ophthalmic services, or whether it results from variation between clinicians in clinical decision making about the likely benefits of squint surgery.